The impact of institutional culture on employees' job satisfaction performance: Understanding the role of institutional culture on employee job satisfaction and performance (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Employers play a vital role in the maintenance of a healthy culture, beginning with therecruitment and selection of applicants who will share the organization's beliefs and thrive in thatculture, developing orientation, training, and performance management programmes that outline andreinforce the organization's core values, and ensuring that employees who truly exemplify the valuesreceive the appropriate rewards and recognition. The results of a main survey research indicate that anorganization's culture has a significant influence on the job satisfaction of its employees.When examining the perceptions of police officers (supervisors and non-supervisors) on theorganisational factors that lead to job satisfaction, it was shown that organisational traits are a moreaccurate predictor than individual factors.The majority of researchers who participated in the study were in their middle years, according to areview of the data. In terms of its focus on cooperation (3.41), assertiveness (3.34), stability (3.32),attention on people (3.29), and readiness to take chances, participants ranked the organization's cultureas moderate (3.29). (3.29). (3.17).